A case of Covid-19-associated invasive pulmonary mucormycosis in a pediatric patient with a newly diagnosed diabetes - L. Pekova; M. Gulubova; M. Hadzhi; M. Mitev; S. Angelova (Respiratory Medicine Case Reports, 2022)
Mucormycosis is a rare, potentially life-threatening disease that is growing during the Covid-19 pandemic. This study reports a case of an 11-year-old patient with fatal Covid-19-related pulmonary mucormicosis and diabetes mellitus with ketoacidosis. The diagnosis was set post mortem. It was based on histochemical detection of the causative agent. Massive hemoptysis due to erosion of a large pulmonary vessel caused mechanical asphyxia and lethal outcome. Pulmonary mucormycosis may be highly suspected in patients with long-term Covid-19, poorly controlled diabetes mellitus with ketoacidosis, and corticosteroid therapy. Early diagnosis and treatment with Amphotericin B are potentially curative options for this invasive fungal infection and can led to better outcome.